2017
DOI: 10.1038/bjc.2016.427
|View full text |Cite
|
Sign up to set email alerts
|

Soluble VE-cadherin in metastatic breast cancer: an independent prognostic factor for both progression-free survival and overall survival

Abstract: Background:Patients with metastatic breast cancer (MBC) represent a heterogeneous group, with large differences in outcomes from individual patients. VE-cadherin, an endothelial-specific cadherin, was shown to promote tumour proliferation and angiogenesis. Soluble VE-cadherin has been recently associated to breast cancer progression. This study was designed to investigate the prognosis significance of soluble VE-cadherin in hormone-refractory MBC.Methods:Between 2004 and 2007, 150 patients with a fully documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…VE-Cadherin is a well-known factor for increased vascular permeability in estrogen-positive breast cancer 57 and its expression correlates with poor survival prognosis in human gastric cancer and can therefore be used as a biomarker 58,59 . VE-Cadherin expression has been related to melanoma 60 and breast cancer progression 61 . Nevertheless, the presence of VE-Cadherin in exosomes or the possible effects that these vesicles may have in the tumorigenic potential of breast cancer cells has not been previously determined.…”
Section: Discussionmentioning
confidence: 99%
“…VE-Cadherin is a well-known factor for increased vascular permeability in estrogen-positive breast cancer 57 and its expression correlates with poor survival prognosis in human gastric cancer and can therefore be used as a biomarker 58,59 . VE-Cadherin expression has been related to melanoma 60 and breast cancer progression 61 . Nevertheless, the presence of VE-Cadherin in exosomes or the possible effects that these vesicles may have in the tumorigenic potential of breast cancer cells has not been previously determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that interaction of BC cells with endothelial cells leads to phosphorylation of VE-cadherin and disruption of endothelial adherent junction [ 24 ]. High levels of serum VE-cadherin were significantly correlated to a shorter progression-free and overall survival [ 25 ]. We can assume that the presence of tumor and tumor-related EVs in the neo-adjuvant patients or a short period after surgery in the adjuvant patients induced tissue and vascular damage prior to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, high CDH5 immunohistochemical expression was a significant risk factor for hematogenous recurrence and was a predictor of survival in locally advanced GC treated by surgery alone. Serum soluble CDH5 could be measured and was an independent prognostic factor in breast cancer (29); therefore, serum CDH5 should be evaluated in patients with GC in the future. The inhibition of CDH5 may serve as a target for the prevention of tumor angiogenesis and hematogenous metastasis in GC.…”
Section: Discussionmentioning
confidence: 99%